(untitled) (Research, Society and Development, 2021)
Currently, despite numerous scientific and technological advances in the area of parasitological diagnoses and in the field of collective health, intestinal parasittosis is still a serious public health problem. They have cosmopolitan distribution, being highly prevalent both in developing and developed countries. Among these parasitic infections, giardiasis, caused by the protozoan Giardia duodenalis, is considered the most common in humans. Its diagnosis is usually carried out through conventional microscopy, however, given its current importance molecular methods have been developed for its detection. The objective of this work is to characterize morphologically and molecularly clinical samples of children positive for Giardia duodenalis in the municipality of Parnaíba, Piauí. Fecal samples were processed according to faust’s method, where positive samples were purified for further molecular characterization. Then, the genetic material was extraction and conventional PCR was performed, through the amplification of segments of the bg and tpi markers. Subsequently, the sequencing of the isolates was elaborated to identify the assemblages. A total of 15 confirmed cases of giardiasis were analyzed in inhabitants of the municipality of Parnaíba-PI, all of which were stratified and characterized as belonging to assemblage A, in which 13 cases (86.6%) reported diarrheal symptoms and nine participants (60%) reported weight loss. Studies are still needed to deepen the knowledge about enteroparasitosis, since there is a lack of more information about the pathogen and a large part of the population is poorly understood regarding the transmission and symptomatology of these, which corroborates the epidemiological data.